Properties and selection of aluminum alloys - Anderson, Kevin (Metallurgist); Weritz, John; Kaufman, J. G. 1931- (ASM Handbook ;, 2019)
"Volume 2B covers the metallurgy, processing, fabrication, properties, and performance of aluminum alloys. The articles in the first section of the volume provide details on the selection of aluminum alloys to meet specific design and performance criteria. The next section presents in-depth datasheets for standard grades of wrought and cast aluminum alloys. The datasheets are designed for easy look up of details on alloy metallurgy, processing effects on properties, and fabrication characteristics. The volume appendices address aluminum alloy temper designations and definitions, aluminum filler metal selection, nominal compositions and composition limits for wrought and cast aluminum alloys, and typical room temperature physical properties of wrought aluminum alloys."--